Effectiveness of The Food Sector Msme Assistance Program Effectiveness During The Pandemic of Covid 19 To Improve Community Welfare - Adli, Khairul Nur; Pranitasari, Diah; Anhar, Muhammad (Indonesian journal of business, accounting and management, 2022)
This study aims to determine the effectiveness of community empowerment through micro-enterprise assistance in improving the welfare of meatball traders in Jakarta which has been carried out by Dompet Dhuafa. The research strategy used in this research is a descriptive quantitative method with a qualitative approach . Descriptive method is a method used to describe, explain, record and analyze conditions what is and is happening from the results of the interview. Collecting data and analyzing data by seeking opinions from the subjects studied using a questionnaire to determine the effectiveness of the mentoring program . The population in this study were all meatball traders who participated in mentoring in Jakarta. With a total population of 50 small traders. The type of sampling chosen in this study was purposive sampling . The sample considerations in this study are meatball traders who are still actively selling and meatball traders who are actively participating in the Dompet Dhuafa mentoring program in work program 5, starting in 2017 (PTM 5). The number of samples is 50 MSME/PTM "saturated samples". The primary data obtained was processed using MS Excel. Statistical analysis of data in this study is descriptive analysis. The results of this study indicate that: (1) In the group mentoring program: the first group meeting is considered effective by members of PTM 5; secondly, group monitoring related to business development is considered less effective by members of PTM 5; thirdly, monitoring of healthy and halal production processes is considered to be less effective by members of PTM 5. (2) In increasing the capacity of partners through training: first, training on entrepreneurship motivation is considered effective by members of PTM 5; secondly, food safety training and training qualitative test were considered less effective by members of PTM 5; the three institutional trainings were considered effective by PTM 5 members. (3) In terms of financial assistance, PTM 5 members considered it quite effective, they felt very helped by the existence of the financial assistance program. *CRITICAL:  Do Not Use Symbols, Special Characters, or Math in Paper Title or Abstract.